Regulation of the Intestinal Stem Cell Pool and Proliferation in Drosophila - Simona Trubin; Dhruv B. Patel; Aiguo Tian (Cells)
Understanding the regulation of somatic stem cells, both during homeostasis and in response to environmental challenges like injury, infection, chemical exposure, and nutritional changes, is critical because their dysregulation can result in tissue degeneration or tumorigenesis. The use of models such as the Drosophila and mammalian adult intestines offers valuable insights into tissue homeostasis and regeneration, advancing our knowledge of stem cell biology and cancer development. This review highlights significant findings from recent studies, unveiling the molecular mechanisms that govern self-renewal, proliferation, differentiation, and regeneration of intestinal stem cells (ISCs). These insights not only enhance our understanding of normal tissue maintenance but also provide critical perspectives on how ISC dysfunction can lead to pathological conditions such as colorectal cancer (CRC).